Developing of guided inquiry-based biochemistry practicum guidebook - Widyaningrum, Diyah Ayu; Wijayanti, Titik (Jurnal Pendidikan Biologi Indonesia, 2018)
There were no practicum guidebook in Biochemistry hands-on activity at IKIP Budi Utomo, Malang city, East Java-Indonesia. The purposeof this study was to develop a guided inquiry-based biochemistry practicum guidebook for students of IKIP Budi Utomo. The development of guidebook followed the 4D-Thiagajaran model which has 4 stages, namely define, design, develop, and disseminate. The types of the data in this study were qualitative and quantitative. The qualitative data was obtained from the validator suggestions. The quantitative data was obtained through validator assessment scores and legibility tests. The instruments used to collect data included validation sheets and questionnaires. The results showed that the practicum guidebook validation percentages were 93.48% (material experts), 100% (learning media expert), and 81.5% (teacher) which were categorized as very feasible. It can be concluded that the biochemistry practicum guidebook is highly suitable to be implemented.